THE ARCHITECTURE OF ENGINEERED UNDERDEVELOPMENT: DECONSTRUCTING THE INFORMATIONAL AND INSTITUTIONAL PARADIGMS OF POST-SOVIET AUTOCRACY - Mahmudjon Kuchkarov (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract: Contemporary Western political economy has largely coalesced around two dominant paradigms to explain the persistence of authoritarianism and economic stagnation in the Global South and post-Soviet space: the “informational autocracy” model articulated by Sergei Guriev and Daniel Treisman, and the “inclusive versus extractive institutions” framework developed by Daron Acemoglu and James A. Robinson. While these theories offer sophisticated descriptive mechanisms of modern dictatorial survival and institutional failure, this article argues that they suffer from a structural, teleological bias that obscures the exogenous geopolitical and economic forces driving post-Soviet autocracy. Drawing upon the analytical framework of Dr. Mahmudjon Kuchkarov, this paper conducts a critical comparative analysis of these models. It exposes the latent ideological functions within Guriev’s and Robinson’s works—specifically, their tendency to naturalize underdevelopment as an endogenous institutional failure rather than a deliberate neocolonial strategy. By contrasting the post-1945 “development model” applied to resource-poor Japan with the post-1991 “underdevelopment model” applied to the resource-rich former Soviet Union, this article introduces Kuchkarov’s thesis: that post-Soviet kleptocracy, systemic poverty, and corruption are not evolutionary errors, but engineered mechanisms designed to facilitate capital extraction to Western financial centers. The paper concludes that true institutional inclusivity must begin with academic inclusivity, using the marginalization of foundational epistemological work—such as Kuchkarov’s Human Language Theory—as a case study of how intellectual suppression sustains extractive regimes.